PENGARUH SUBSITUSI OIL PALM SHELL (OPS) + SUPERPLASTICIZER TERHADAP KUAT TEKAN, TARIK DAN BERAT BETON - Raja Marpaung (PILAR, 2012)
The aim of this study is to  determine and compare the value of compressive strength, tensile strength, heavy volume, and workabilities concrete produced from a mixture of concrete with substitution of oil palm shells with coarse aggregate with a variation of 10%, 20%, 30%, 40% and 50% by adding additional ingredients (additives) superplasticizer. Quality concrete planned in this study is  K-250.  The test result shows  that the oil palm shell concrete mixed by adding additional ingredients (additives) superplasticizer, resulting in compressive strength, tensile strength of concrete is lower and lighter weight concrete, the more the percentage of oil palm shells is substituted  with coarse aggregate, the more decline the compressive strength, tensile strength of concrete will be, but  weight concrete is also lighter. Meanwhile, by adding  superplasticizer to the mixture of oil palm shell concrete, workabilities and the concrete compressive strength  produced will be  better than normal  mixture concrete.  Percentage reduction in compressive strength  obtained in a mixture of oil palm shell concrete superplasticizer + 28 days is 25.72% - 67.39%., The decrease percentage  in tensile strength is obtained in a mixture of oil palm shell concrete age of 28 days which is  33,43 d 28 days which is 10,67% in the variation OPS 10%, whereas in the OPS mixture of 40% and 50% ratio ft / fc' is very small.